Optimization of Selo Bonang Tourism in Panduman Village Through Identification and Construction of Singing Stone Valley - Markus Apriono; Bayu Aprillianto; Regina Niken Wilantari; Nining Ika Wahyuni; Eko Suwargono; Isti Fadah; Siti Maria Wardayati; Intan Nurul Awwaliyah (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Selo Bonang is one of the new tours that can be an attraction with various potentials possessed. Selo Bonang itself has a lot of potential, both from the cultural aspect, the topography of the location, then the variety of economic products sold by the local community, and there is a unique thing that has the potential to become iconic because it is still not found in other locations, namely the existence of stone sites that have tones and can be enjoyed in the Argopuro valley, the site is called "Singing Stone Valley". This devotion aims to compose and construct the musical stone arrangement into a harmonious tone. This activity will be useful in attracting tourists so that they can play musical instruments from natural stones with the natural atmosphere of the Argopuro valley.